Coronary artery calcification is common on nongated chest computed tomography imaging. Issue 7 (16th March 2017) - Balakrishnan, Revathi; Nguyen, Brian; Raad, Roy; Donnino, Robert; Naidich, David P.; Jacobs, Jill E.; Reynolds, Harmony R.
Abstract : Background: Coronary artery calcification as assessed by computed tomography (CT) is a validated predictor of cardiovascular risk, whether identified on a dedicated cardiac study or on a routine non‐gated chest CT. The prevalence of incidentally detected coronary artery calcification on non‐gated chest CT imaging and consistency of reporting have not been well characterized. Hypothesis: Coronary calcification is present on chest CT in some patients not taking statin therapy and may be under‐reported. Methods: Non‐gated chest CT images dated 1/1/2012 to 1/1/2013 were retrospectively reviewed. Demographics and medical history were obtained from charts. Patients with known history of coronary revascularization and/or pacemaker/defibrillator were excluded. Two independent readers with cardiac CT expertise evaluated images for the presence and anatomical distribution of any coronary calcification, blinded to all clinical information including CT reports. Original clinical CT reports were subsequently reviewed. Results: Coronary calcification was identified in 204/304 (68%) chest CTs. Patients with calcification were older and had more hyperlipidemia, smoking history, and known coronary artery disease. Of patients with calcification, 43% were on aspirin and 62% were on statin medication at the time of CT. Coronary calcification was identified in 69% of reports when present. Conclusions: A high prevalence of coronary calcification was found in non‐gated chest CT scans performed for non‐cardiac indications. In one‐third, coronary calcification was not mentioned in the clinical report when actually present. In this population of patients with cardiac risk factors, standard reporting of the presence of coronary calcification may provide an opportunity for risk factor modification.